2009
DOI: 10.1007/s10158-009-0086-x
|View full text |Cite
|
Sign up to set email alerts
|

GABAA- and AMPA-like receptors modulate the activity of an identified neuron within the central pattern generator of the pond snail Lymnaea stagnalis

Abstract: To examine the neurochemistry underlying the firing of the RPeD1 neuron in the respiratory central pattern generator of the pond snail, Lymnaea stagnalis, we examined electrophysiologically and pharmacologically either "active" or "silent" preparations by intracellular recording and pharmacology. GABA inhibited electrical firing by hyperpolarizing RPeD1, while picrotoxin, an antagonist of GABA(A) receptors, excited silent cells and reversed GABA-induced inhibition. Action potential activity was terminated by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…8A), is a ubiquitous neurotransmitter that generally mediates inhibitory synaptic transmission. In several species of gastropod molluscs, GABAergic neurotransmission has been implicated in behaviors such respiration [56], olfaction [57,58], feeding [5962] and reproduction [63], however its role specifically in Nudibranchs remains poorly understood [64]. Comparative immuno-localization of GABA in the CNS of several Nudibranch species, including Tritonia , revealed clusters of conserved GABAergic neurons in the cerebral and pedal ganglia [64].…”
Section: Resultsmentioning
confidence: 99%
“…8A), is a ubiquitous neurotransmitter that generally mediates inhibitory synaptic transmission. In several species of gastropod molluscs, GABAergic neurotransmission has been implicated in behaviors such respiration [56], olfaction [57,58], feeding [5962] and reproduction [63], however its role specifically in Nudibranchs remains poorly understood [64]. Comparative immuno-localization of GABA in the CNS of several Nudibranch species, including Tritonia , revealed clusters of conserved GABAergic neurons in the cerebral and pedal ganglia [64].…”
Section: Resultsmentioning
confidence: 99%
“…Given that Lymnaea has a wide range of neurotransmitters similar to those in cephalopods (Tansey, 1979; Di Cosmo et al, 2004, 2006; D’Aniello et al, 2005; Moccia et al, 2009) this makes it a useful testbed for preliminary studies on more advanced molluscs. What is more, Lymnaea has a well-researched behavioral repertoire (Winlow and Polese, 2014) so that both the cellular and behavioral actions of anesthetics can be studied.…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%
“…Magnesium salts have been used as an adjunct to clinical anesthesia (Elsersy et al, 2017; Elsonbaty and Isonbaty, 2017), and may attenuate vincristine-induced neuropathic pain (Bujalska et al, 2009) and chronic diabetic neuropathic pain (Rondon et al, 2010) in rat models, where they have also been found to reduce inflammatory pain (Srebro et al, 2018), probably due to the blocking action of Mg 2+ on NMDA receptors. Such receptors are well known both in cephalopods (Di Cosmo et al, 2004, 2006) and gastropods (Moccia et al, 2009). Thus, it is probable that magnesium chloride acts as a muscle relaxant and as a mild central sedative analgesic (James, 1992; De Oliveira et al, 2013).…”
Section: Actions Of Anesthetics On Cephalopod Molluscsmentioning
confidence: 99%
“…On the other hand, larger areas of injury may release chemical messages, such as concentration gradients of vascular endothelial growth factor (VEGF) and stromal derived factor-1α (SDF-1α), that recruit circulating endothelial progenitor cells to the wound edge in order to replace damaged endothelium [5-10]. The break in the anatomic integrity of vascular endothelium is significantly larger in subjects undergoing medical interventions, such as deployment of endovascular devices and percutaneous transluminal coronary angioplasty [2,11,12]. Such a heavy loss of ECs from the vascular wall dampens the beneficial effects of reconstructive surgery and prompts the quest for pharmacological treatments aiming at restoring the continuity of endothelial monolayer [2,11-13].…”
Section: Introductionmentioning
confidence: 99%
“…Such a heavy loss of ECs from the vascular wall dampens the beneficial effects of reconstructive surgery and prompts the quest for pharmacological treatments aiming at restoring the continuity of endothelial monolayer [2,11-13]. Accordingly, the de-endothelialisation of arterial vessels may cause thrombi formation and neointimal hyperplasia, giving raise to a process termed as "in-stent restenosis" (ISR) which renarrows the arterial lumen [2,11,12]. Drug-eluting stents (DES) may be implanted during or after angioplasty to inhibit neointimal hyperplasia and prevent ISR [2,12,14].…”
Section: Introductionmentioning
confidence: 99%